Emissions of Fe(II) due to the undersea volcano of El Hierro - Santana González, Carolina; Santana Casiano, Juana Magdalena; González Dávila, Melchor (2014)
The Fe(II) is an essential micronutrient for the phytoplankton grow, and due to its low solubility in seawater it is found in the 0.2-2 nM range for the north Atlantic ocean. However the eruptive stage process and the subsequent hydrothermal stage occurred in the undersea volcano at the southeast of the El Hierro Island, Spain has risen the concentration of TFe(II) in the waters nearest to the main cone. Two cruises were carried out on March and October 2013, inside the VULCANO project, in order to detect any variation in concentrations of TFe(II) due to emissions after the eruptive process. Flow injection chemiluminescence using luminol as reagent was used to determine the concentrations of TFe(II). The results confirm an important positive anomalies in TFe(II) which coincide with negative anomalies in pH located in a secondary cone, during October cruise. It is also observed maximum values in TFe(II) at the surface associated to chlorophyll a maximum and to the sea bottom, showing the important influence of surface runoff, organic complexation and particle re-suspension processes. Temporal study in the station located over the secondary cone with positively anomalies in pH was carried out during 4 days. It showed an important variability in both pH and TFe(II) concentrations that indicated the volcanic area was affected by intermittent events of hydrothermal fluids in vent that remains in the volcano cone one and a half year after the eruptive phase has ceased. The increased TFe(II) concentrations and the low associated pH values may be acting as an important fertilization event in the seawater around the volcano at the Island of El Hierro providing optimal conditions for the regeneration of the area. 207 207 1